REPRESENTATION OF ISLAMIC AND MINANGKABAU CULTURAL VALUES IN THE DESIGN OF THE GREAT MOSQUE OF WEST SUMATERA - Kurniati, Feni
Through architectural design competition, a number of buildings to represent local culture are produced in Padang, one of them is the Great Mosque of West Sumatera. This study attempts to view the architect’s creative process in designing the mosque; see the acceptance of public towards the mosque; and discover the links between them regarding the representation of that architectural product. Data were collected through open interviews with the architect to uncover the design process, with the grand juries to obtain judgement criteria, and with the public to look at the acceptance level towards the design. The subjects of interview, grand jury and community were selected purposively. The community were selected in the main criterion of having visited the great mosque. The data were recorded verbatimly and then analyzed through the process of coding and clustering. The research indicated that the architect’s creative process is divided into four stages: the understanding of the project, the conceptualization of the design, the development of the design, and the process of synthesis of some ideas related to the notion of Islam, the local culture of Minangkabau, and the architectural ideas. The research also suggested that public tend to give appreciation towards the novelty of form and decoration, as well as the monumental impression of the building. Related to the aspect of Islam, the appreciation emerged from the use of Islamic decoration. In addition to the local culture, the most appreciated aspect is the form of gonjong and the impression of the local culture in exterior decoration. This study concluded that there is congruence of the concepts between architect’s representation and community acceptance. The congruence indicated a mutual relationship: the architect read and took the values of society to be represented in the design, and vice versa, the community read the design and then is reflected it into their ownselves.